Stream Sediments Geochemistry from Dili and Manatuto Districts. Implications for mineral resources exploration - Nogueira, Pedro (2015)
A field campaign was conducted aiming to verify a significant number of mineral occurrences in the geological literature of Timor-Leste. During this campaign a set of 45 samples of stream sediments were collected and analysed for 35 elements. The results of this campaign are presented discussing the confirmation and refute of the occurrences.